Primary intestinal T cell lymphomas in Indian patients - In search of enteropathic T cell lymphoma - Shet Tanuja; Karpate Arti; Bal Munita; Gupta Sudeep; Gujral Sumeet; Nair Reena (Wolters Kluwer Medknow Publications, 2010)
Objective: This series of six intestinal T cell lymphomas (ITCL) attempts to document enteropathy-associated T cell lymphoma (EATCL) in India. Materials and Methods: A total of six ITCL were selected from 170 gastrointestinal lymphomas in last 10 years. Results: The cases studied included EATCL (4), ITCL with a CD4 positive phenotype (1) and ITCL NK/T cell type (1). Of the four EATCL, two occurred in the ileum, one in right colon and one in duodenum. In three EATCL cases, there was history of celiac disease or lactose intolerance and enteropathic changes were noted in the adjacent mucosa. These tumors had CD3+/CD8+/CD56 (+/-)/CD4-/ Granzyme B+ immunophenotype. One EATCL was monomorphic small cell type (type II EATCL) with a CD3+/CD8-CD56+/CD4-/ Granzyme B+ phenotype. EBER- ISH (Epstein Barr virus coded RNA′s- in situ hybridization) revealed positive tumor cells in ITCL NK/T cell type and in bystander cells in three EATCL. Conclusion: ITCL are rare in Indian patients but do occur and comprise a mixture of the enteropathic and non-enteropathic subtypes.